IC 6364 Milling Method And Cost At The Conglomerate Mill Of The Calumet & Hecla Consolidated Copper Co. - C. Harry Benedict (The National Institute for Occupational Safety and Health (NIOSH), 1930)
This paper presents the details of milling practice and costs at the conglomerate mill of the Calumet & Hecla Consolidated Copper Co., Lake Linden, Mich., and is one of a series on milling methods being published by the Bureau of Mines. GENERAL DESCRIPTION The mines of the Calumet & Hecla. Consolidated Copper Co. are located in the Keweenaw Peninsula of northern Michigan. The mines of this district lie in a belt not over 4 miles wide and 100 miles long, which contains more or lees commercial ore. The Calumet & Hecla properties are the farthest north, except for the Seneca, of the operating mines. The district borders on Lake Superior, and by means of the Portage and Torch Lake waterways the largest lane vessels, can transport coal and other supplies from the lower Lakes directly to the company docks.